Everything you need to know about smoking - Keyishian, Elizabeth (New York : Rosen Pub. Group, 2003)
Discusses the dangerous effects of smoking, why people start, why it's so hard to quit, and how to stop smoking.
Includes bibliographical references (p. 60-61) and index.
Keywords: Tobacco use -- Juvenile literature; Smoking -- Juvenile literature; Youth -- Tobacco use -- Juvenile literature; Smoking